Beastly - Flinn, Alex. (New York : HarperTeen, 2008)
A modern retelling of "Beauty and the Beast" from the point of view of the Beast, a vain Manhattan private school student who is turned into a monster and must find true love before he can return to his human form.
Keywords: Beauty, Personal -- Fiction; New York (N.Y.) -- Fiction